Implementing digital signatures for healthcare enterprises: the case of online disability evaluation reports. (3rd May 2005) - Tulu, Bengisu; Li, Haiqing; Chatterjee, Samir; Hilton, Brian; , Thomas Horan
This paper presents a conceptual security framework and a case study of a digital signature solution implementation for a healthcare organisation that provides disability evaluation services for various government agencies and private companies. One service the company provides for its clients is online disability report generation and electronic report submission. When generating these disability reports, the signature of the examining physician is required for submission. The current process used by the company involves the manual collection of signatures. To streamline this process, and to meet legal and client requirements, the company investigated a digital signature solution. A security framework previously proposed was utilised to guide the implementation of the digital signature solution. This security framework consists of eight sequential stages. An in-depth analysis of the first seven stages for this case is provided, including guidelines for choosing digital signature solutions, vendor analyses and implementation issues.